2022
DOI: 10.1021/acsomega.2c02517
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study to Quantify Fracture Propagation in Hydraulic Fracturing Treatment

Abstract: Hydraulic fracturing plays an important role in the commercial development of unconventional oil and gas, which is directly related to the production of oil and gas wells. An accurate evaluation is critical for hydraulic fracturing, but it is urgent to propose a quantitative assessment of hydraulic fracturing fracture propagation for realizing hydraulic fracturing fracture propagation and multiposition permeability measurement under an in situ stress environment. Herein, a true triaxial stress loading and perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…[1][2][3][4] Pulse hydraulic fracturing has been widely proven to increase rock fatigue damage and reservoir permeability by circulating injection fluid. [5][6][7][8][9] Wei et al 10 carried out physical experiments on fracture propagation and concluded that more fractures were generated around the wellbore by pulse hydraulic fracturing than by conventional hydraulic fracturing. Zhuang et al 11 found that the cyclic pulse water pressure could control the fracture propagation when studying the fracture propagation of granite under various pulse modes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] Pulse hydraulic fracturing has been widely proven to increase rock fatigue damage and reservoir permeability by circulating injection fluid. [5][6][7][8][9] Wei et al 10 carried out physical experiments on fracture propagation and concluded that more fractures were generated around the wellbore by pulse hydraulic fracturing than by conventional hydraulic fracturing. Zhuang et al 11 found that the cyclic pulse water pressure could control the fracture propagation when studying the fracture propagation of granite under various pulse modes.…”
Section: Introductionmentioning
confidence: 99%
“…They use a large amount of proppant to prop up fractures and improve effective reservoir permeability 1–4 . Pulse hydraulic fracturing has been widely proven to increase rock fatigue damage and reservoir permeability by circulating injection fluid 5–9 . Wei et al 10 carried out physical experiments on fracture propagation and concluded that more fractures were generated around the wellbore by pulse hydraulic fracturing than by conventional hydraulic fracturing.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al 8 conducted research on the seepage behavior of fracture networks after hydraulic fracturing of shale and concluded that the seepage channels formed during the process can significantly enhance the permeability of shale. In addition, hydraulic fracturing is also used in the commercial development of oil and gas wells to increase production 9–11 . These findings demonstrate that hydraulic fracturing has a substantial impact on rock permeability.…”
Section: Introductionmentioning
confidence: 85%
“…In addition, hydraulic fracturing is also used in the commercial development of oil and gas wells to increase production. [9][10][11] These findings demonstrate that hydraulic fracturing has a substantial impact on rock permeability.…”
mentioning
confidence: 96%
“…In the aspect of hydraulic fracture morphology detection, acoustic emission (AE) technology and computed tomography (CT) scanning have been applied to hydraulic fracturing tests. Many scholars have obtained the spatial geometric shapes of fractures and porosity in samples through CT scanning technology. Ju et al constructed heterogeneous sandstone and homogeneous sandstone models under hydraulic fracturing by using CT three-dimensional (3D) reconstruction and discussed the influence of the horizontal stress ratio on the spatial distribution and shape of fracturing fractures. Li et al used high-frequency AE to monitor true triaxial hydraulic fracturing of coal.…”
Section: Introductionmentioning
confidence: 99%